2011
DOI: 10.1590/s0103-05822011000100007
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de bebidas e refrigerantes por adolescentes de uma escola pública

Abstract: Objective: To evaluate the consumption of beverage and soft drinks by adolescents of a public school in São Paulo, Brazil.Methods: 71 adolescents (aged between 14 to 17 years old) from both genders, attending a technical school in the metropolitan area of São Paulo, answered the following questions: the kind of beverage taken during meals, the places where soft drinks were consumed and the main reason related to this intake.Results: The most frequent consumed beverage was the industrialized fruit juice (38.1%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
16

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 18 publications
0
8
0
16
Order By: Relevance
“…Studies have shown that regular soft drinks are the second beverage most widely consumed during the meal by adolescents (28.6%) [13]. Another important finding was that as the age of the children increased, the consumption of carbonated drinks, including soft drinks, increased while milk intake decreased significantly [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that regular soft drinks are the second beverage most widely consumed during the meal by adolescents (28.6%) [13]. Another important finding was that as the age of the children increased, the consumption of carbonated drinks, including soft drinks, increased while milk intake decreased significantly [14].…”
Section: Introductionmentioning
confidence: 99%
“…No presente estudo, 10,4% do sexo feminino e 14% do sexo masculino relataram o consumo de refrigerante junto com a alimentação escolar, resultado inferior ao encontrado em outra pesquisa (20) , na qual 29% dos alunos (maioria do sexo feminino) tomavam refrigerante durante as refeições, enquanto outro estudo (21) observou um maior consumo de refrigerante durante almoço e lanches (55%).…”
Section: Discussionunclassified
“…The adolescents reported that the main reasons that led to the consumption of diet and light /zero foods were the habit and keep fit ( Figure 1B). Nowadays it is observed among adolescents, the significant increase in the consumption of industrialized beverages, especially fruit juices and soft drinks, replacing some foods, such as, for example, milk and its derivatives, water and natural fruit juices 14 . In the present study, soda was the most consumed zero food by the adolescents.…”
Section: Methodsmentioning
confidence: 99%